Response surface methodology approach to study the influence of PEG and water in cellulose acetate dialysis membranes - Idris, Ani; Lee, Kuan Yet; Noordin, M. Y.; Chan, Mieow Kee (Penerbit UTM Press, 2008)
Flat sheet asymmetric dialysis membranes were fabricated using phase inversion method from polymer solution consisting of cellulose acetate, acetic acid, polyethylene glycol (PEG) and distilled water. The effect of acetic acid/PEG ratio and the distilled water content in the dialysis membrane were being investigated with respect to the urea clearance performance. Response surface methodology (RSM) was used to design the experiments and analysed the results obtained. The analysis revealed that the significant factor that affects the cellulose acetate dialysis membrane performance in terms of urea clearance is the ratio of acetic acid/PEG. Dialysis membrane with higher ratio of acetic acid/PEG gives higher urea clearance percentage due to the formation of finger like macrovoids. The relation between the urea clearance and the ratio of acetic acid/PEG in the given range of 4 – 14, was a quadratic model and the mathematical model suggested could adequately describe the performance indicators within the limits mentioned.